Private Midwives’ Perceptions on Barriers and Enabling Factors to Voluntary Counselling and HIV Test (VCT) in Bali, Indonesia - Lubis, Dinar Saurmauli; Wulandari, LPL; Suariyani, Ni Luh Putu; Tresna Adhi, Kadek; Andajani, Sari (UI Scholars Hub, 2019)
In Indonesia, more than half of pregnant women seek antenatal care (ANC) at private midwifery clinics. The midwives play an important role in advocating for voluntary counseling and testing (VCT) uptake among pregnant women during ANC. This study examined midwives’ perception of barriers and enabling factors with regards to refer pregnant women for HIV testing. The study was conducted in Denpasar City and Badung District, two localities in Bali with high HIV prevalence. Two focus groups discussions with 15 private midwives and five in-depth interviews were conducted. Data were transcribed verbatim and thematic analysis methods were used to examine patterns emerging from the data. Results showed that private midwives face personal barriers in the form of stigma as well as institutional barriers such as VCT operational hours that limit how and when they refer women for VCT. Barriers are strengthened by lack of support or reward from the health office. However, opportunities for integrated and comprehensive support systems within the health system and supportive social environment which would make it easy and rewarding for midwives to refer women to VCT clinics were seen as enabling factors. Increasing uptake of VCT is a necessity for eliminating mother to child HIV transmission.